“Manual de procesos para el comisariato Kerly del cantón La Maná, provincia de Cotopaxi, año 2023.” - Añarumba Coro, Vanessa Elizabeth (2023)
The current research was aimed to design a manual process for Kerly market, of La Maná canton, Cotopaxi province, year 2023. The problems inmersed in the investigation are constant. In addition, claims and complaints from customers for poor service or delay, shipment of products which are not agreed with the request and damaged merchandise due to mishandling are also mentioned. The methodology used in the project to reach the objective was bibliographic research. It was very important because it allowed to validate the information to define the various concepts that were used during the development of the project. Descriptive research was used; this type of research helped to visualize the characteristics of the object of study and conditions that affect the current state of the market. Field research was used for conducting the applied surveys to the population under study, as well as the interview to the manager who owns the market. The inductive method was necessary to use for the project because based on the client's experience, so more generalized criteria can be issued. The deductive method was of great help for deducing particular aspects from the interview to the business manager and for the emition of conclusions and recommendations. The applied techniques to collect information were: the interview which was directed to the owner, as well as the surveys applied to customers. The technical scientific foundation was used through administration, processes, and customer service. The population was integrated by the owner and 1500 frequent customers. Two instruments were designed, a questionnaire for interviews whose content was formed by open and closed questions and a survey which was structured with options on a Likert scale. The validation of the instruments for both interview and surveys was through experts and with professors of Business Administration career who collaborated with their knowledge and observations for the respective calculation of populations at Kerly market.